Intense plastic deformation of high-purity cast beryllium - Vasilev, A.A.; Stetsenko, S.P.; Vasilenko, R.L.; Malykhin, D.G.; Stoyev, P.I.; Khovrich, S.V.; Trembach, O.V.; Kovtun, K.V. (Вопросы атомной науки и техники, 2020)
The effect of intense plastic deformation on the mechanical properties, structure, and texture of high-purity cast beryllium was studied. For the first time, angular pressing of high-purity cast beryllium was carried out at temperatures of 600 and 500 °C. It is shown that the degree of grain refinement during angular pressing into a strip reaches a significant value. In one deformation cycle, the grain is crushed from 3 mm to 10 μm. The temperature dependences of the mechanical properties of the material of extruded billets in the initial state and after recrystallization annealing at a temperature of 650 °C for one hour were studied. It has been established that the best mechanical properties have samples of material deformed at 600 °C and subsequent annealing at 650 °C for an hour.